Protective Effect of Bifidobacterium lactis JYBR-190 on Intestinal Mucosal Damage in Chicks Infected With Salmonella pullorum - Yang, Liangyu; Chen, Yuanhong; Bai, Qian; Chen, Xi; Shao, Yunteng; Wang, Ronghai; He, Fengping; Deng, Ganzhen (Frontiers in Veterinary Science, 2022)
Pullorum is one of the most serious diseases that endanger the chicken industry. With the advent of the era of anti-antibiotics in feed, the replacement of antibiotics by probiotics has become the focus and hotspot of related research. In this study, hematoxylin-eosin (H&E) staining, immunohistochemistry (IHC) and enzyme-linked immunosorbent assay (ELISA) were used to observe the structural changes of intestinal mucosa in chicks infected with Salmonella pullorum, and to analyze TNF-α, IL-10 and IFN-γ and secreted immunoglobulin A (sIgA) levels. The results showed that the intestinal villus height, villus height to crypt depth ratio (V/C), muscle layer thickness and thickness of duodenum, jejunum and cecum in the JYBR-190 group were significantly higher than those of the infection group and antibiotic group. Furthermore, the levels of proliferating cell nuclear antigen (PCNA), sIgA and IL-10 in JYBR-190 group were significantly increased, whereas the expression of TNF-α and IFN-γ was significantly decreased. Taken together, Bifidobacterium lactis JYBR-190 has a protective effect on intestinal mucosal damage in chicks infected with Salmonella pullorum.